Coordination, organizations, institutions, and norms in agent systems X : COIN 2014 International Workshops, COIN@AAMAS, Paris, France, May 6, 2014, COIN@PRICAI, Gold Coast, QLD, Australia, December 4, 2014, revised selected papers /: COIN 2014 International Workshops, COIN@AAMAS, Paris, France, May 6, 2014, COIN@PRICAI, Gold Coast, QLD, Australia, December 4, 2014, revised selected papers. (2015) - Unknown
No abstract available